Debt and Interest Rates: The U.S. and the Euro Area - Jeffrey Frankel; Menzie D. Chinn (Kiel Institute for the World Economy (IfW), 2007)
We find that real interest rates paid on government debt depend significantly upon current and expected future levels of debt, in Europe as in the US. But this result only emerges when we condition on foreign interest rates, illustrating financial international integration. The previously strong effect of debt on US interest rates has been diluted by the addition of 2004-2006 data to the sample, perhaps reflecting the effect of massive purchases of US securities by foreign central banks. Another finding is that the asymmetry in the effect of US interest rates on European interest rates has not disappeared with the coming of European Economic and Monetary Union in 1999, as one might have thought.
Keywords: E43; F41; E58; 330; interest rates; inflation; debt; financial integration